Đầu tư trực tiếp nước ngoài vào bất động sản tại Việt Nam - Lý Đại, Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The paper analyzes the foreign direct investment in real estates (FDIRE) in Vietnam by a macroeconomic approach. With a Time Varying Coefficients Bayesian Vector Autoregressive model (TVC-BSVAR) and a monthly time-series sample over 01/2017–02/2023, the evidence records that for an increase of 1 billion USD in FDIRE, the short-run economic growth rate raises by 2% and the stock market value increases by 1% right in the first month, and the impact decays after 12 months. The FDIRE is also persistent over time when it contributes largely to its future variation, with up to 50% after 12 months. This result implies that the FDIRE can be expected to be high if it is high but would be difficult to come back to its initial value if it reduces substantially.
Keywords: Foreign Direct Investment; Real Estates; Vietnam